Treatment of Excessive Gingival Display using CAD-CAM Guided Aesthetic Crown Lengthening and Surgical Lip Repositioning as an Alternative to Orthognathic Surgery: A Case Report - Apeksha Annigeri; Abhirami Sureshbabu; Vinayak Kumbhojkar; Nivethitha Divavakaran (Journal of Clinical and Diagnostic Research)
Excessive Gingival Display (EGD), commonly known as a gummy smile, is a significant aesthetic concern. The factors responsible for EGD include altered passive eruption, a short or hyperactive upper lip, vertical maxillary excess, or a combination of these. The classic treatment for severe cases of vertical maxillary excess and EGD is orthognathic surgery. However, Aesthetic Crown Lengthening (ACL) and Lip Repositioning (LR) can offer a conservative, minimally invasive and reliable alternative for treating EGD. This case report focuses on managing EGD using a conservative, minimally invasive mucosal strip surgical technique for a 23-year-old female patient who presented with a severe gummy smile. Management was planned with a combination of ACL and LR. A CAD-CAM milled surgical guide was designed and printed by superimposing Stereolithography (STL) files of digital impressions, photographs and Digital Imaging and Communications in Medicine (DICOM) files from a Cone-beam Computed Tomography (CBCT) scan to provide a suitable and predictable reference for ACL. The LR was performed by resecting a mucosal strip and coronally repositioning the upper lip, thereby reducing the depth of the upper vestibule to restrict lip elevation during smiling, which in turn reduces the gingival display. A substantial reduction of 4 mm of gingival display was seen post-operatively. ACL and LR aided with CBCT can be considered a safe and conservative treatment option for EGD.